2008
DOI: 10.1002/jbt.20212
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Nrf2 in the transcription activation domain by casein kinase 2 (CK2) is critical for the nuclear translocation and transcription activation function of Nrf2 in IMR‐32 neuroblastoma cells

Abstract: The antioxidant-activated transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) regulates the induction of cytoprotective genes against chemical toxicity and oxidative injuries. The role of phosphorylation in Nrf2 activation has been suggested but remains elusive. We report that phenolic antioxidant/pro-oxidant tert-butylhydroquinone (tBHQ) induced two forms of the Nrf2 protein in neuroblastoma cells (IMR-32), which migrated as distinctive bands on SDS-PAGE. In vitro treatment with λ λ phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
136
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(142 citation statements)
references
References 30 publications
6
136
0
Order By: Relevance
“…Conventional cell signaling studies have suggested that Nrf2 might be regulated by protein phosphorylation (2,6,15,18,36,44). Previously, we presented data suggesting that GSK-3␤ (glycogen synthase kinase 3␤) influences the nuclear exclusion and inactivation of Nrf2 (37)(38)(39).…”
mentioning
confidence: 91%
“…Conventional cell signaling studies have suggested that Nrf2 might be regulated by protein phosphorylation (2,6,15,18,36,44). Previously, we presented data suggesting that GSK-3␤ (glycogen synthase kinase 3␤) influences the nuclear exclusion and inactivation of Nrf2 (37)(38)(39).…”
mentioning
confidence: 91%
“…In HEK293T cells, Salazar et al (23) showed that Nrf2 is phosphorylated by GSK-3␤ and that this phosphorylation localizes it to the cytoplasmic compartment; according to their report, diminished entry of Nrf2 into the nucleus resulted in impaired Nrf2-induced activation of ARE-driven gene promoters. In contrast, in neuroblastoma cells phosphorylation of the Neh4 (Nrf2-ECH homology 4) and Neh5 domains of Nrf2 positively influenced its nuclear translocation as well as its transactivation activity (24). In another study, Fyn kinase-mediated phosphorylation of Tyr 568 in Nrf2 was reported to regulate its nuclear export and degradation (25).…”
mentioning
confidence: 94%
“…Modification of cysteine residues by ROS-induced stress allows the dissociation of Nfr2 from Keap1 (22). There are, however, other regulatory mechanisms such as phosphorylation and proteosomal degradation which are also important in regulating Nfr2 activity (23,24). The significance of these mechanisms could not be assessed in this study, although they might explain some of the discrepancy between the detected immunohistochemical staining of Keap1 and Nfr2.…”
Section: Discussionmentioning
confidence: 81%